2007
DOI: 10.3349/ymj.2007.48.1.69
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Human Papillomavirus Infection in Korean Non-Small Cell Lung Cancer Patients

Abstract: Human papillomavirus (HPV) infection is a co-carcinogen of lung cancer and contributes to its pathogenesis. To evaluate the prevalence of HPV infection, polymerase chain reaction (PCR) was employed to detect HPV 16, 18, and 33 DNA in tumor tissues of 112 patients with non-small cell lung cancer (NSCLC) who underwent curative surgery from Jan. 1995 to Dec. 1998 at Severance Hospital, Seoul, Korea. The patients consisted of 90 men and 22 women. Nineteen patients were under 50 years old (17%), and 92 patients (82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 35 publications
0
17
0
2
Order By: Relevance
“…There is the possibility that the use of nested-ISH could have led to over-amplification of HPV DNA. A recent Korean study using PCR methods for detecting HPV 16, 18 and 33 showed low prevalence of the high-risk genotypes averaging 10% and no association with smoking status or sex (30). A study from India that looked at 40 patients with lung cancer showed again low prevalence (5%) of HPV 18 and absence of HPV 16 (31).…”
Section: %) --------------------------------------------------------mentioning
confidence: 99%
“…There is the possibility that the use of nested-ISH could have led to over-amplification of HPV DNA. A recent Korean study using PCR methods for detecting HPV 16, 18 and 33 showed low prevalence of the high-risk genotypes averaging 10% and no association with smoking status or sex (30). A study from India that looked at 40 patients with lung cancer showed again low prevalence (5%) of HPV 18 and absence of HPV 16 (31).…”
Section: %) --------------------------------------------------------mentioning
confidence: 99%
“…A large sample investigation reported that HPV DNA infection rate was 21.7% in 2468 lung carcinomas (11). HPV infection is considered a cocarcinogen of lung cancer and its contribution to pathogenesis has been evaluated (12)(13)(14)(15)(16)(17)(18). However, even in Asian populations, the prevalence discrepancy of HPV infection in lung cancer patients was also found with the geographic variations and tumor types.…”
Section: Introductionmentioning
confidence: 86%
“…Although HPV 16 has been detected more frequently than HPV 18 in both squamous cell carcinomas and adenocarcinomas [111,113,115,117,133], HPV 18 predominance has been demonstrated by other researchers [118,130,134] in both squamous cell carcinomas and adenocarcinomas. The higher prevalence of HPV 33 infections in Korean lung cancer patients compared to other Asian and Western countries [115] has not been confirmed in the US and Western European countries.…”
Section: Hpv and Lung Cancermentioning
confidence: 95%
“…HPV infection has been detected in smoking and nonsmoking patients with lung squamous cell carcinoma or adenocarcinoma [112]. Although smoking has been more frequently noted in heavy smokers than in patients with a low daily cigarette consumption and non-smokers [122,127], other investigators [115] have not found any correlation between HPV and smoking status. There has been no correlation between HPV infection and gender, age, stage, grade, and lymph node status of the carcinomas [115,122,125,127].…”
Section: Hpv and Lung Cancermentioning
confidence: 99%